Between fascination and distance. The reception of Discipline and Punish in spanish historiography - Vázquez García , Francisco (Política y Sociedad, 2025)
This article aims to evaluate the reception of Discipline and Punish, the work of the philosopher Michel Foucault, in the field of Spanish historiography. To do so, we use a methodology inspired by the social history of reading and the sociology of the processes of intellectual importation. We begin by pointing out the peripheral and dispersed character of its initial reception, quite distant from the university departments of contemporary history. This absence is explained by alluding to the state of the Spanish historiographical field and two stages are differentiated in the course of this reception. In the first (1978-1994), the work was received with great interest, and its arguments were combined with those adduced by Marxist critical criminology. In the second (1995-2020), a critical distancing prevailed, underlining the inadequacy of the Foucauldian account with respect to the historical reality of the Spanish penal system. Finally, it is pointed out that, beyond the misunderstandings of the reading that Spanish historians made of Foucault’s work, it has decisively marked the development of penal historiography in our country, reaching the rank of a classic text.